Treatment patterns and outcomes of second/third-line therapy in advanced non-small cell lung cancer with actionable genomic alterations (RECAP) - Hanxiao Chen; Xiangjiao Meng; Ling Cai; Wei Lei; Yu Tang; Xi Shi; Leilei Ma; Jun Zhao (Clinical & Experimental Metastasis, 2026)
Treatment choices for metastatic non-small-cell lung cancer (NSCLC) after first-line targeted therapy progression are heterogeneous. This study aimed to characterize real-world treatment patterns and outcomes of advanced NSCLC harboring actionable genomic alterations (AGAs) in second- (2 L) or third-line (3 L) settings. This retrospective cohort study across six Chinese centers included stage IV NSCLC patients with confirmed AGAs. Therapies were divided into six categories: targeted monotherapy (T), targeted combinations (T+), chemotherapy monotherapy (C), chemotherapy combinations (C+), anti-angiogenic monotherapy (A), and other regimens (O). The primary outcome was the treatment pattern. Secondary outcomes included biomarker testing and effectiveness. A total of 658 patients were enrolled, with the majority harboring EGFR mutations ( n = 590, 89.7%). In the 2 L-enrolled group ( n = 602), T use declined from 75.3% in the 1 L setting to 49.3% in 2 L, while utilization of A + C increased to 16.5%. Within the EGFR-mutant subgroup, therapeutic sequences were highly dependent on 1 L TKI generation and T790M resistance status. Over half (51.1%) of T790M-negative patients continued T in 2 L following progression on 1 L first- or second-generation TKIs. Among the 3 L-enrolled patients ( n = 56), A + C (35.7%) and C (14.3%) were predominant. The overall median real-world progression-free survival for the 2 L-enrolled group was 7.4 months in the 2 L setting (7.5 months for the EGFR-mutant subgroup) and 5.4 months in 3 L. This multicenter real‑world cohort predominantly comprised patients with EGFR‑mutant NSCLC, with smaller numbers of other AGA subtypes. Targeted therapies remain the cornerstone of later-line advanced NSCLC management. The prevalent real-world reliance on continued TKI therapy, even in T790M-negative patients, highlights the clinical dilemma of limited post-resistance options and the need to integrate emerging novel therapeutics.